2007
DOI: 10.1097/blo.0b013e31803c75b4
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity Pulsed Ultrasound Does Not Enhance Distraction Callus in a Rabbit Model

Abstract: Low-intensity pulsed ultrasound has been reported to have a positive effect when applied during the consolidation phase of distraction osteogenesis and bone transportation, but the optimal application time has not been determined. We used a rabbit model to determine whether low-intensity pulsed ultrasound applied during the distraction and early consolidation phases of tibial lengthening would have a positive effect on regenerated bone formation. Radiographic analysis showed no differences in regenerated callu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
8
1
Order By: Relevance
“…These results can be explained by the fact that at early stages of DO, the distraction gap is filled mostly with hyper-cellular soft tissue and less mineralized tissue, thus facilitating the transmission of LIPUS. In contrast, the results in study [21] did not support the application of LIPUS at the distraction and early stages of consolidation periods.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…These results can be explained by the fact that at early stages of DO, the distraction gap is filled mostly with hyper-cellular soft tissue and less mineralized tissue, thus facilitating the transmission of LIPUS. In contrast, the results in study [21] did not support the application of LIPUS at the distraction and early stages of consolidation periods.…”
Section: Discussioncontrasting
confidence: 62%
“…Of which, 31 studies were eliminated after reviewing the abstracts which clearly showed these papers did not meet the criteria. Of the 19 potentially eligible articles retrieved in full text [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], 2 were excluded as they used high intensity ultrasound (2 W/cm 2 ) [27,28] and 2 studies were published in 2 articles each and were thus considered as one study for the purpose of the research [11,12,23,24], leaving 15 eligible studies included in the systematic review (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The benefit of the applied mechanical signal continued even during the 4-week rest period, perhaps suggesting the additional bone and vessels formed during the treatment period acted as a secondary resource for osteogenic and stem cells or the mechanism triggered by the signal remained active even after the stimulus had subsided [42]. The robust osteogenic effects of this noninvasive treatment observed after the 8-week experimental period also emphasizes some advantages over tissue-engineering approaches that rely on stem cells and/or physical signals such as ultrasound, electrical currents, or electromagnetic fields [1,11,28,43]. Not only is application of the physical signal noninvasive, simple, and inexpensive, it also does not require incubation time, bears no substantial risk of transmitting infections and diseases, and is unlikely to promote development of tumors from electrical waves.…”
Section: Discussionmentioning
confidence: 89%
“…Tissue-engineering approaches, including stem cells and growth factors [18,24] or externally applied signals such as stimulation with electric currents [7,11], ultrasound [10,43], or laser [28], are promising in overcoming these problems, but they also have several shortcomings. Current cell culture-based techniques require considerable resources to reach the number of required cells, bear risks for transfer of infectious diseases, and involve invasive surgery [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation